The Origin and Evolution of the Term "You Qing" in Traditional Chinese Medicine - Yachen ZHAO; Xiaoling XIONG (Yixue yu zhexue, 2025)
As a common Chinese word, "You Qing" usually means emotional attachment or interpersonal affection. After the introduction of Buddhism, the Sanskrit word Sattva was translated as "You Qing", specifically denoting sentient beings—those possessing consciousness and perception—as opposed to insentient entities, which together comprise all things in the world. Beginning in the Tang Dynasty, this Buddhist connotation of "You Qing"—referring to sentient beings—gradually entered the medical corpus of Traditional Chinese Medicine (TCM). By the Ming and Qing dynasties, it became widely cited in various medical formularies and pharmacopoeias, fostering new theoretical developments in TCM. These included concepts such as the principle of sentience and medicines derived from sentient beings, ultimately leading to the notion of flesh-blood sentient medicinals, which has been passed down through generations. This study also finds that in TCM surgery, You Qing was used to describe conditions containing purulent discharge—an understudied definition omitted from many major dictionaries and in need of supplementation. The concept of "flesh-blood sentient medicinals" does not merely refer to animal-derived drugs, but rather to substances that tonify human qi and blood and originate from sentient beings.